Recurrent spindle cell lipoma mimicking myofibroblastic tumor with myxoid changes: Cytological diagnostic dilemma - -, Shveta; Smita, Singh; Manoj, Andley; Monisha, Choudhury (Indian Journal of Case Reports, 2020)
Spindle cell lipoma (SCL) is an uncommon subtype of benign lipomatous neoplasms with a rare probability of the local recurrence. Correct cytological diagnosis is essential for the patient management. Surgical excision is the treatment of choice. Sometimes, it gets very difficult to reach a correct cytological diagnosis without a histomorphology or immunology. We are reporting a case of recurrent SCL in an adult male and emphasise on distinguishing cytological features for a correct and accurate diagnosis on cytomorphology. The correct cytological diagnosis of recurrent SCL is essential to distinguish it from malignant lipomatous and other soft tissue tumors.